Are Malaysian police really stressed? understanding their potential stress factors - Rasdi, Irniza; Muhamad Saliluddin, Suhainizam (Community Health Society Malaysia, 2015)
Background: A large number of studies have been conducted on mental health among police officers but data for Malaysian police are rarely available.